Study of Gob-Side Entry Retaining Technology with Roof Cutting under Upper Roadway Condition - Xingen Ma; Manchao He; Xuewei Sun; Jianfeng Li; Gang He; Enze Zhen (Shock and Vibration, 2021)
Gob-side entry retaining technology with roof cutting (GERRC) has been widely used in flat and near-flat coal seam conditions, but its application under inclined coal seam is still very deficient. In order to further improve the application system of GERRC and overcome the application difficulties under special geological conditions, this paper takes the 43073 working face of Yixin coal mine as an example to research the GERRC with upper roadway under gently inclined thick coal seam. Firstly, the difficulties in the upper entry retaining with inclined coal seam are analyzed and the corresponding key technologies and system designs are put forward. Subsequently, the roof cutting and upper entry retaining are designed in detail according to geological conditions of test working face, and the roof cutting and pressure releasing effect is analyzed by numerical simulation to expound the stress distribution and pressure releasing mechanism of surrounding rock. Finally, the upper entry retaining field test is carried out to verify the feasibility and applicability of the technology and related designs. Through field monitoring, it is found that the weighting step increases significantly, the weighting strength decreases effectively on the roof cutting side, and the pressure relief effect is obvious. Meanwhile, the maximum roof to floor convergence is 361 mm and the maximum shrinkage of both sides is 280 mm, so the retained entry can meet the reuse requirement of adjacent working face.